ANALISIS PERBANDINGAN HARGA SAHAM, NILAI SAHAM DAN ABNORMAL RETURN SAHAM PADA PERUSAHAAN IFR (INTERNET FINANCIAL REPORTING) DAN NON-IFR (NON INTERNET FINANCIAL REPORTING) (Studi Empiris Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Finta Isfa Nofianti; Emrinaldi Nur DP; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study examines the difference of stock price, stock value and abnormal return between the company of IFR and the company of NON-IFR. And examines the difference of stock price, stock value and abnormal return between the company of higher degree of information transparency in IFR and the company of lower degree of information transparency in IFR. Population of this research was registrated companies at BEI. The samples used in this research was 99 companies who applied IFR and 99 companies who non applied IFR. The method of determining the sample is by using purposive sampling method, while the data processing methods used by researcher are the independent sample t-test analysis. The result of study shows that there are difference of stock price, stock value and abnormal return between the company of IFR and the company of NON-IFR. And there are difference of stock price and stock value between the company of higher degree of information transparency in IFR and the company of lower degree of information transparency in IFR. But the abnormal return between the companies with higher degree of information transparency in IFR do not differ from the companies with lower degree of information transparency in IFR.Keywords: Stock Price, Stock Value, Abnormal Return, Degree of Information Transparency and Internet Financial Reporting (IFR)